PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP PENGELOLAAN DANA DESA - Karunia, Tiara; Maria, Maria; Aryani, Yuli Antina (Jurnal Riset Terapan Akuntansi, 2025)
The purpose of this study is to examine the influence of accountability and transparency on village fund management in Semende Darat Laut Subdistrict, Muara Enim Regency. The phenomenon of poor quality of village fund management, including cases of alleged budget irregularities, demonstrates the importance of implementing good village governance principles and practices. The study used a quantitative method with a survey of 90 respondents consisting of officials and village leaders from ten villages. SPSS 25 was used for multiple linear regression data analysis. The findings of the study show that accountability significantly improves village fund management, as does transparency. Simultaneously, both variables have a significant positive impact on village fund management. Village officials, acting as agents, are responsible to the community as principals, in accordance with agency theory. Therefore, improving accountability and transparency is crucial in achieving effective, efficient, and accountable village fund management. Keywords: accountability, transparency, village fund management.